New Identities from a Combinatorial Approach to Generalized Fibonacci and Generalized Lucas Numbers - da Silva, Robson [UNIFESP] (2018)
We present here some new identities for generalizations of Fibonacci and Lucas numbers by combinatorially interpreting these numbers in terms of numbers of certain tilings of a 1 x m board. As a consequence, some new interesting identities involving the ordinaries Fibonacci and Lucas numbers are derived.